(untitled) (Physical Education, Health and Social Sciences, 2025)
In the context of growing socio-economic disparities and environmental degradation, understanding how targeted behavioural interventions affect consumption decisions within networked environments remains a pressing challenge, particularly in developing countries like Pakistan. This study investigates the effects of informational nudges and taxation mechanisms on individual choices over positional and ordinary goods in a controlled network experiment. The objective is to examine how variations in network centrality—such as being in a core, intermediate, or peripheral position—influence responsiveness to policy treatments aimed at enhancing social welfare. A behavioural game-theoretic model was implemented through a 30-period experimental design where participants allocated endowments between a positional good (y) and a non-positional good (x), under five distinct treatments: baseline, nudge-all, nudge-center, tax-all, and tax-center. Results reveal that (1) universal taxation leads to the highest average per-period payoff but also the greatest reduction in positional good consumption, (2) centralised nudges have limited impact on periphery nodes but significantly reduce overconsumption in core nodes, (3) participants with higher network centrality are more belief-sensitive and welfare-reactive, and (4) efficiency gains are maximised when interventions are aligned with network position. These findings, grounded in the Pakistani socio-economic context, underscore the importance of designing position-specific behavioural policies to promote equitable consumption and sustainable welfare improvements.